The Influence Of Electronic Payment Systems And Impulsive Buying On Online Shopping Intentions At Shopee Indonesia - Nafisa Khaerani Affap; Alldila Nadhira Ayu Setyaning (International Journal of Education, Vocational and Social Science, 2024)
This research is motivated by the existence of online shopping intention in E-commerce Shopee Indonesia influenced by electronic payment system, impulsive buying and behavioral control with company trust as the mediator. This study aims to determine the variables: electronic payment system, impulsive buying, trust, and behavioral control affect online shopping intention in E-commerce Shopee Indonesia. This research is quantitative research. The method used in this study is Structural Equation Modeling (SEM) with data collection using purposive sampling. Data samples will be taken from E-commerce Shopee Indonesia users who mostly use the E-payment system. In this study, data was taken in May 2024 from 249 respondents. There are five hypotheses in this study and all four hypotheses are accepted. However, impulsive buying does not have a positive effect on company trust.